(untitled) (Bulletin KNOB, 2006)
Four hundred years after Rembrandt’s birth all sorts of exhibitions are to be seen in the Dutch museums. An effort was made to show different aspects of the artist’s oeuvre and ask new questions as regards realization and interpretation. What happened to the houses in which the artist lived and what value can be attributed to this? After a wrong location had initially been designated and in doubt about what to do with the house in which Rembrandt died (Rozengracht 184 Amsterdam), it is exactly one hundred years ago that the foundation Stichting Het Rembrandthuis turned the premises Jodenbreestraat 4 into a museum. The aim was a set-up that did justice to the spirit of the genius of Rembrandt by means of a layout in harmony with the historical starting-point, being a largely reconstructed 17th-century shell. New-development architect K.P.C, de Bazel executed this with the consent of architect A.W. Weissman and art connoisseur J.P. Veth. They were against bringing in 17th-century furniture, because they feared that the large public would mistakenly associate it with Rembrandt, but the furniture was brought in all the same. The modernist, detached early 20th-century approach was given new shape around 1998 with the construction of the extension by architects Sas and Jansma/Zwarts. The matter of the removal of De Bazel’s interior from the old part of the building was contested in court, even though a seemingly 17th-century design merges with what may still be authentic. There are some interesting similarities with the Dürerhaus, which served as an example for Amsterdam in 1906, but had already been acquired by the city of Nürnberg in 1826 and was made into a museum in 1871. Just as Rembrandt, Dürer functioned as a national symbol, a national figure to be proud of. (In retrospect) both artists were thought to deserve a more spacious and comfortable accommodation than was actually available, and this is also evident from the painstaking reconstruction of the buildings. It is ironical that Rembrandt had bought a house in Amsterdam beyond his means, and moreover in a neighbourhood that was on its way down from a social point of view. In the 19th and 20th century depopulation, redevelopment and industrial compression afflicted Amsterdam, and under these circumstances it is a miracle that the Amsterdam Rembrandthuis was preserved. Things went differently for Rembrandt’s birthplace in Leiden, which due to ignorance was drastically altered in the 19th century and swept away in the 20th century after a few impracticable attempts at reconstruction had been made. The fact that the Dürerhaus in Nürnberg survived the war is also a lucky coincidence. Unfortunately, this does not go for Dürer’s birthplace, which was bombed and rebuilt in a contemporary form after the war. As far as research and justification are concerned in connection with a drastic reconstruction, Amsterdam can learn from Nürnberg once again, where in 2006 a congress, an exposition and various publications have been devoted to the Dürerhaus.